(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Aqueous extract of Kigelia africana leaves have been utilized for the synthesis of silver (AgNPs) and copper-silver bimetallic nanoparticles (Ag-CuNPs) that were generally found to be spherical and oval in shape. The synthesized nanoparticles were characterized using UV-Vis, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy/energy dispersive X-ray analysis (SEM/EDX), and transmission electron microscopy (TEM). The antimicrobial activities were evaluated against both gram-negative and gram-positive strains of bacteria. The UV-Vis and FTIR techniques revealed the formation of nanoparticles and the active components were adsorbed on the surface of the particles thereby stabilizing the nanoparticles. The SEM reveals uniform microspheres of AgNPs and anisotropic particles for Ag-CuNPs. TEM shows the size of synthesized particles. The nanoparticles inhibited the growth of both gram-negative and gram-positive bacteria. The bimetallic nanoparticles synthesized from aqueous extract of K. africana leaves showed greater inhibition against Escherichia coli as compared to the monometallic nanoparticles. The AgNPs was more effective for the reduction of 4-nitrophenol and 4-nitroaniline as compared to Ag-CuNPs. The results of this study confirmed that Kigelia africana leaf and fruit aqueous extract can successfully reduce metallic ions to synthesize metallic nanoparticles that have antimicrobial and biocatalytic properties.